سبعۃ اَحرف و قراءاتِ قرآنیہ ؛ایک تحقیقی جائزہ: A Research Review of Sab‘a Aḥraf and Recitation of the holy Qur’an in different ways - Abdul Rauf, Hafiz; Adnan Siddiq, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
“This Quran has been revealed in seven different ways; so, recite it in the way that is easier for you.” This hadith is Recurrent in meaning. The narrator Imam Abu Ubaid Qasim Bin Salam (R.A) has elucidated its recurrence. Imam Abn-e- Jouzi (R.A) has collected all its ways in a Journal. What is meant by “Seven Words” in this Hadith? It has been a controversial point among the ulemas and scholars. And no doubt, it has been regarded as the most difficult debate of Uloom-ul- Quran. There have been severe controversies in this regard, so far as Allama Ibn-e - Arabi has mentioned thirty-five sayings. Some of them are as following: Some think these are the ways of recitations of seven famous Qaries. Some think that it means all the ways of recitations. But “Seven” does not means the number 07, because in Arabic language, it is used to describe the plenty of something. Qazi Ayyaz from Earleir Ulemas had the same opinion, while in the later period; Shah Wali-Ullah also had the same views. Some think that it means seven dialects of Arab Tribes. Imam Abu Hatim Sajestani (R.A) determined the name of these languages. They are Quraish, Hazial, Teem, Al-Rubab, Azd, Rabbia, Hawazan, and Saad bin Abi-Bakar. Hafiz Abn-e- Jareer Tibri (R.A) agreed to this school of thought. The fourth famous saying is that of Imam Tehavi (R.A.) he says that although he Holy Quran has been revealed in the dialect of Quraish. But it was difficult for the people of other tribes, which came of different areas of Arab. That is why, in the beginning, they were permitted to recite the Holy Quran in their local languages, and the words or ways were determined by the holy prophet (P.B.U.H) himself. Later, it was prohibited. There remained only the one way of recitation in which the holy Quran was revealed. HAzrat Sufian bin Aiena (R.A), Abn-e-Wahab (R.A) and Hafiz Ibn-e- Abdul Bar (R.A) agreed to this opinion. Famous interpreter Allama Nizamul Din Nishapori (R.A) says that it means the following differences in the recitation. Differences between Singular and Plurals Differences between Muscular and Feminine Differences of the causes of Araabs Differences of Morphology (Formation of Words) Differences of syntax (Sentence Structure) Differences of the ways which changes words Differences of dialects Allama Abn-e- Qutaiba, (R.A), Imam Razi Qazi (R.A) and Abu Bakar(R.A) and Abn-e Aljuzri (R.A) also adopted this saying of Allama Nisahpuri.(R.A).